The Role of Muhammadiyah Islamic Movement in Hacking a New Map of Local Culture in Indonesia - Riska Aprillianti; Dayang Safira Bella Avilia; Romelah (Universitas Muhammadiyah Malang, 2022)
This article aims to examine the movement of Muhammadiyah. Muhammadiyah's commitments since its establishment until now is that Muhammadiyah has positioned itself as a pure creed-based Islamic da'wah movement. Muhammadiyah's role in creating a local culture for modern culture, Muhammadiyah has several programs launched in the field of culture. To examine those backgrounds, this article uses a historical approach to the normative juridical method. This article found that Muhammadiyah's program in the field of culture is an effort intended to develop an appreciation of art that is in line with the views of Muhammadiyah's beliefs. One of the applications of Muhammadiyah's cultural program is the development of culture-based education. Muhammadiyah is expected to be able to carry out its strategic role in terms of culture very optimally. In forming a progressive culture, Muhammadiyah does not only need a commensurate movement strategy but at the same time has a building of thought that goes beyond, so that it appears as a carrier of a progressive alternative Islamic message with a strong and superior character. From the womb of Muhammadiyah was born the transformation of Indonesian culture which is religious and progresses parallel to and even superior to other nations. Here the important role of actualizing the view of progressive Islam as declared in the One Century Congress, which is accompanied by the strategy of the enlightenment movement (a movement that liberates, empowers, and advances) in all its orientations and steps.